Touch-free tissue dispensing device - Mohd Zaki, Nurul Shahira; Nik Dzulkefli, Nik Nur Shaadah; Abdullah, Rina; Ismail, Syila Izawana; Omar, Suziana (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
In this paper, an innovative solution for the everyday issue of tissue dispensing is presented. With billions of tissues distributed daily, the current dispensers often face challenges, as revealed in studies of frequently damaged units. The primary objective was to enhance this fundamental item, aiming to simplify users’ lives. The key innovation lies in granting users control over the tissue dispenser’s rolling mechanism. Introducing the Arduino UNO microcontroller-powered smart tissue dispenser. Operated by a stepper motor, the dispenser reacts to the user’s needs. Activation occurs when the infrared sensor detects hands, prompting the motor to release the appropriate amount of tissue. It’s like witnessing magic, yet it’s simply the ingenuity of technology at play. The software for the Arduino UNO, serving as the project’s controller, is compiled, and uploaded using the Arduino IDE. The performance of this automatic tissue dispenser indicates success in addressing common issues and facilitating effortless tissue retrieval.